Thermally Stable and Regenerable Platinum–Tin Clusters for Propane Dehydrogenation Prepared by Atom Trapping on Ceria - Xiong, Haifeng; Lin, Sen; Goetze, Joris; Pletcher, Paul; Guo, Hua; Kovarik, Libor; Artyushkova, Kateryna; Weckhuysen, Bert M.; Datye, Abhaya K. (Angewandte Chemie (International ed.), 2017)
Ceria (CeO2) supports are unique in their ability to trap ionic platinum (Pt), providing exceptional stability for isolated single atoms of Pt. The reactivity and stability of single‐atom Pt species was explored for the industrially important light alkane dehydrogenation reaction. The single‐atom Pt/CeO2 catalysts are stable during propane dehydrogenation, but are not selective for propylene. DFT calculations show strong adsorption of the olefin produced, leading to further unwanted reactions. In contrast, when tin (Sn) is added to CeO2, the single‐atom Pt catalyst undergoes an activation phase where it transforms into Pt–Sn clusters under reaction conditions. Formation of small Pt–Sn clusters allows the catalyst to achieve high selectivity towards propylene because of facile desorption of the product. The CeO2‐supported Pt–Sn clusters are very stable, even during extended reaction at 680 °C. Coke formation is almost completely suppressed by adding water vapor to the feed. Furthermore, upon oxidation the Pt–Sn clusters readily revert to the atomically dispersed species on CeO2, making Pt–Sn/CeO2 a fully regenerable catalyst. Isolated platinum single atoms are active but not selective for alkane dehydrogenation. Platinum single atoms self‐assemble into subnanometer platinum–tin clusters during reaction. The spent catalyst readily reverts to an atomically dispersed state after oxidation treatment without the need for added chlorine.